Defects of properties in mathematics : quantitative characterizations - Ban, Adrian I.; Gal, Sorin G., 1953- (Singapore ; River Edge, NJ : World Scientific, 2002)
'This book introduces a method of reasearch which can be used in various fields of mathematics. It examines, in a systematic way, the quantitative characterizations of the'deviation from a (given) property', called the'defect of a property', in: set theory; topology; measure theory; real, complex and functional analysis; algebra; geometry; number theory; fuzzy mathematics'--P. [2] of cover.
Includes bibliographical references (p. 337-348) and index
Keywords: Mathematics; Fuzzy mathematics; Deviation (Mathematics)